Recognition of Facial Expressions in ADHD - J Gordon Millichap (Pediatric Neurology Briefs)
The identification of facial expressions of four emotions (joy, anger, disgust, and sadness) was investigated in 30 children aged 7-12 years with ADHD, predominantly hyperactive-impulsive subtype, at Free University of Brussels, Belgium.